(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyze the effect of academic self-efficacy on academic AI dependency with the mediating role of academic stress and critical thinking in students of the Faculty of Economics and Business, State University of Surabaya. The study used a quantitative approach with a sample of 100 active students selected through a purposive sampling technique. Data were collected using a Likert scale questionnaire that measured academic self-efficacy, academic stress, critical thinking skills, and academic AI dependency. Data analysis was carried out using Structural Equation Modeling-Partial Least Square (SEM-PLS) using SmartPLS 4 through testing the measurement model (outer model), structural model (inner model), and testing the mediation effect. The results showed that academic self-efficacy did not significantly influence academic AI dependency. However, academic self-efficacy had a significant negative effect on academic stress and a significant positive effect on critical thinking. In addition, academic stress had a significant positive effect on academic AI dependency, while critical thinking had a significant negative effect on academic AI dependency. These findings suggest that strengthening critical thinking skills and managing academic stress is important to encourage wiser and more productive use of AI in higher education settings.